Zakat in Islam - Fathullah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2018)
Zakat is a number of assets that must be issued by the followers of Islam to be given to the eligible groups, such as the poor and the like, in accordance with established by sharia. Zakat belongs to the pillars of Islam and becomes one of the most important elements in enforcing Islamic law. Therefore zakat law is mandatory for every Muslim who has fulfilled certain conditions. Zakat is also a form of worship such as prayer, fasting, and others and has been arranged in detail based on Al-Quran and Sunna. Here, we elaborate types of zakat, its term and how to calculate and issue them. Keyword: Zakat In Islam